The Modigliani and Miller Propositions: The History of a Failed Foundation for Corporate Finance?. (September 2014) - Dempsey, Mike
<x xml:space="preserve">Abstract</x> The Modigliani and Miller (MM) propositions provide a foundation for corporate finance theory. Nevertheless, this paper argues that their adoption has led to a disengagement of such theory from the humanity of business, as well as, more broadly, from concepts of corporate strategic management. As a result, the context within which textbooks allow corporate investment and financial decisions to take place is severely distorted from reality. The paper argues that we require the context of behavioural and strategic corporate management if we are to accommodate the reality of business, the behaviour of formalised groups, and an ethical dimension to business.